ABSCISIC ACID-INSENSITIVE 5-ω3 FATTY ACID DESATURASE3 module regulates unsaturated fatty acids biosynthesis in Paeonia ostii. (April 2022) - Li, Yang; Wang, Xiruo; Zhang, Xiao; Liu, Zheng'an; Peng, Liping; Hao, Qing; Liu, Zenggen; Men, Siqi; Tong, Ningning; Shu, Qingyan
Highlights: The change of ABA content is consisted with that of UFAs during P. ostii seed development. PoABI5 promotes the transcription of PoFAD3 instead of PoFAD2 . Silencing of PoABI5 represses the transcription of PoFAD3 . Both PoABI5 and PoFAD3 are induced by ABA. The expression of PoABI5 affected the response of PoFAD3 to ABA. Abstract: Paeonia ostii is an authorized novel vegetable oil crop due to its seeds rich in unsaturated fatty acids (UFAs) especially α-linolenic acid (ALA), which overweight the current available edible oil. However, little is known on the regulation mechanism of UFAs biosynthesis during its seed development. Here, we used transcriptome and proteome data combining phytochemistry means to uncover the relationship between abscisic acid (ABA) signaling and UFAs biosynthesis during P . ostii seed development. Based on transcriptome and proteome analysis, two desaturases of omega-6 and omega-3 fatty acid, named as PoFAD2 and PoFAD3 responsible for ALA biosynthesis were identified. Then, an ABSCISIC ACID-INSENSITIVE 5 (ABI5) proteins was identified as an upstream transcriptional factor, which activated the expression of PoFAD3 instead of PoFAD2 . Moreover, silencing of PoABI5 repressed the response of PoFAD 3 to ABA. This study provides the first view on the connection between the function of ABA signaling factors and ALA biosynthesis in the P . ostii seed, which lays the foundation for studies on the regulatory mechanism of ABA signaling involved in the UFAs synthesis during seeds development, meanwhile, it will shed light on manipulation of ALA content for satisfying human demands on high quality of edible oil or healthy supplement.